Exploring the needs for Indigenous Allyship among post-secondary international students in Canada - Yuan, Xuechen (Journal of International Students, 2025)
This mixed-methods study taps into the salient features of knowledge mobilization and sociocultural conditions that shape postsecondary international student experiences with Indigenous cultures and commitment to allyship—a consistent gap identified in the literature. In the qualitative phase, international students from a Canadian university participated in a semistructured interview inviting them to share their Indigenous learning experiences and reflections on their allyship. The quantitative phase involved international students who completed a questionnaire, interpreted with principal component analysis (PCA) and correlation analyses. The findings highlighted several themes underlying international student–Indigenous allyship: multicultural contexts, sources of learning, perceptions of indigeneity, cultural similarities, and sociocultural barriers. Key gaps emerged in the relational contexts of allyship, access to cross-cultural opportunities, and weaving Indigenous-led knowledge in curricula.